Establishment of a novel homogeneous nanoparticle-based assay for sensitive procalcitonin detection of ultra low-volume serum samples - Li P (Dove Medical Press, 2018)
Peng Li,1 Zhenhua Chen,1 Bing Liu,1 Kun Li,1 Hao Wang,1 Li Lin,1 Ling He,1 Jie Wei,2 Tiancai Liu1 1State Key Laboratory of Organ Failure Research, Institute of Antibody Engineering, School of Laboratory Medicine and Biotechnology, Southern Medical University, Guangzhou, Guangdong, People’s Republic of China; 2Department of Clinical Laboratory, Sun Yat-Sen Memorial Hospital, Sun Yat-Sen University, Guangzhou, Guangdong, People’s Republic of China Purpose: Sepsis is a potentially fatal systemic body infection with a significant mortality rate worldwide. Although C-reactive protein (CRP), interleukin-6 (IL-6), and procalcitonin (PCT) might be biomarkers for sepsis diagnosis, PCT is more sensitive and specific than CRP or IL-6. We aimed to establish an efficient immunoassay that precisely detects PCT in human serum for the early diagnosis of sepsis. Materials and methods: We developed a novel amplified luminescent proximity homogeneous assay (AlphaLISA) for the quantitative detection of PCT in serum. In this assay, a pair of antibodies was used to capture PCT in serum and to form sandwich complexes after incubating for 15 minutes at 37°C. Results: PCT concentrations were determined within a linear range of 0.016–100 ng/mL. The limit of detection was 18.6 pg/mL. The results demonstrate that the reproducibility, recovery, and specificity of this assay for PCT meet the requirements of clinical detection. The coefficient of determination (R2) between this method and commercially available enzyme-linked fluorescent assay (ELFA) kits was estimated to be 0.93045 in clinical serum testing. Conclusion: The novel assay for PCT detection was robust with high sensitivity and a broad dynamic range. Compared with conventional heterogeneous detection methods such as ELISA, this assay measured the concentration of the homogeneous form of PCT and provided results that are more accurate within a shorter detection time. We expect that this novel method will be useful for the early screening and prognosis evaluation of patients with sepsis. Keywords: sepsis, procalcitonin, nanoparticles, quantitative detection, homogeneous immunoassay